(untitled) (Research, Society and Development, 2021)
Pitaya has great potential for marketing and processing. However, the lack of knowledge about its cultivation is still a barrier that prevents its diffusion in the country. The objective of this study was to analyze the changes that occur during the growth and ripening of white-fleshed dragon fruit. Physical and physicochemical and chemical fruit characterization analyzes were conducted at several development stages (7, 14, 21, 28, 35 and 42 days after anthesis). Increases in length, fruit mass and pulp, yield and soluble solids were observed, as well as reductions in skin thickness, strength and pulp pH. Significant and important levels in mineral for the human diet were found, especially nitrogen, potassium, calcium, manganese, iron and zinc. Intense changes in seed maturation and biomass accumulation occoured during the fruit growth phase, while in the maturation stage the main changes are related to the improvement of the organoleptic characteristics such as acidity reduction and content of soluble solids, besides the reduction of the mass and thickness of the skin. The ideal harvest point, whereas organoleptic characteristics and visual aspects, is around 35 days, when fruit reached physiological maturity; however, at 42 days, the fruit pulp still had sufficient quality for consumption.